(untitled) (Prosiding Keislaman dan Sains, 2025)
The phenomenon that occurred in 2023, the Indonesian Child Protection Commission (KPAI) revealed that from January to August 2023, there were 2,355 cases of violations of child protection. Of that number, 861 cases occurred in educational units. Islamic religious education is very important to re-awaken students through the practice of the Pancasila Student Profile. Based on the background above, the author created a paper entitled "Analysis of Islamic Religious Education Values ​​in the Pancasila Student Profile." The formulation of the problem in this study is: what are the values ​​of Islamic religious education contained in the Pancasila Student Profile? The purpose of this study is to analyze the values ​​of Islamic religious education contained in the Pancasila Student Profile. This type of research is a library research, namely research that aims to understand the phenomena experienced by research subjects, such as behavior, perception, motivation, actions, and others, holistically, in a descriptive manner. The values ​​of Islamic Religious Education in the Pancasila Student Profile can be seen from: a) The value of aqidah education, namely faith and piety. b) The value of moral education, namely religious morality, personal morality, morality towards humans, morality towards nature, and national morality. c) Sharia values, namely independence, mutual cooperation, global diversity, critical thinking, and creativity. The relevance of the values ​​of Islamic Religious Education to the Pancasila Student Profile can be seen in the elements of Faith, Piety to God Almighty, and Noble Morals which contain the values ​​of aqidah and moral education. The elements of independence, mutual cooperation, global diversity, critical thinking, and creativity contain sharia values. The implications of the Pancasila Student Profile in Islamic Religious Education can be seen from the implementation of the Pancasila Student Profile through school culture, intracurricular learning, co-curricular activities, and extracurricular activities that focus on character building.